Studi tentang Tantangan Strategis dalam Mewujudkan Desentralisasi Pendidikan - Wayan Koster (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Study on Strategic Challenges in Realizing the Educational Decentralization. This study was aimed to obtain data on the implementation of educational decentralization. A meta-analysis was applied in this study, by combining primary and secondary data. The data were obtained from studies held on 1993, 1999, and 2000 by the Ministry of National Education and by the Department of Law. The result revealed that our regional conditions did not contribute to the implementation of educational decentralization. The school management was ineffective and inefficient. Budgets for education were inappropiate. The parent participation was relatively low, but the quantity and quality of human resources in the schools were good enough.